Analisis Dampak Penerapan PJOK Nomor 23 Tahun 2023 Terhadap Sumber Daya Manusia Dalam Skenario Ketidakmampuan Perusahaan Asuransi Memenuhi Ketentuan Ekuitas Minimm - Dwi Eloran; Sitti Rakhman (Jaringan Pemberdayaan Politik Lingkungan Hidup, 2026)
Abstract This study examines the human resources (HR) implications of the Financial Services Authority Regulation (POJK) Number 23 of 2023 on insurance business licensing and institutional arrangements, particularly within the scenario where insurance companies fail to meet the staged minimum equity requirements. The regulation requires conventional and sharia insurance and reinsurance companies to gradually increase their minimum equity by the end of 2026 and 2028, with escalating supervisory sanctions from written warnings to business activity restriction and license revocation imposed on non-compliant companies. While prior studies have extensively discussed the regulation from financial, managerial, and legal perspectives, its consequences for employees remain underexplored. Using a qualitative descriptive method combined with normative-juridical legal analysis based on secondary data statutory regulations, peer-reviewed journal articles, and documented industry cases this study finds that corporate failure to satisfy the equity threshold triggers a chain of organizational responses, including downsizing, restructuring, and in extreme cases, business dissolution, each of which generates job insecurity, diminished organizational commitment, and reduced statutory protection for affected workers, particularly the lowered severance entitlement applicable in bankruptcy-related termination. The study also identifies HR competency gaps emerging from consolidation (KUPA) and sharia unit spin-off requirements. These findings suggest that capital-strengthening policy in the insurance sector carries significant indirect social costs that warrant complementary HR-protective measures from both regulators and industry management.